The Influence Of Perceived Stigma On Anxiety Of People Living With Hiv/Aids (Plwha) In Groups Support Peers Regency Jombang: A Cross-Sectional Study - Widyowati, Agustin; Takariningsi (Journal for Quality in Public Health, 2025)
The problem the health of PLWHA is very complex, not only limited to health physique but also on the aspect psychological, social and spiritual which can influence prognosis. Disorders psychological problems felt by PLWHA, namely anxiety and worry can influenced by perceived stigma. The purpose of the study analyzing perceived stigma towards PLWHA anxiety in Groups Support Peers Regency Jombang. Research This is studies analytic with cross-sectional approach. Population that is all people with HIV AIDS in the Group Support Peers Regency Jombang as many as 666 PLHIV and the number sample​ as many as 250 respondents use formula Slovin. The sampling technique uses a purposive sampling technique that meets the requirements criteria inclusion. The independent variable is perceived stigma and the dependent variable is anxiety of PLWHA. Data collection with questionnaire HIV/AIDS Stigma Instrument-PLWA for measuring perceived stigma and ZSAS for measure variable PLWHA anxiety. Analysis using the Spearman rho test. The results of the study almost all PLWHA experience high perceived stigma as many as 243 respondents (97.2%) and most of them Most PLWHA experience anxiety currently as many as 243 respondents (97.2%). The results of the statistical test obtained a p-value of 0.001 < 0.005 and r = 0.181, which means there is influence between perceived stigma towards PLWHA anxiety in Groups Support Peers Regency Jombang. The high perceived stigma increases anxiety of PLWHA that can impact on his health prognosis so that need effort change perception public for reducing stigma through promotion health.